If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(15 + 6a) = 486 (15 * 7 + 6a * 7) = 486 (105 + 42a) = 486 Solving 105 + 42a = 486 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-105' to each side of the equation. 105 + -105 + 42a = 486 + -105 Combine like terms: 105 + -105 = 0 0 + 42a = 486 + -105 42a = 486 + -105 Combine like terms: 486 + -105 = 381 42a = 381 Divide each side by '42'. a = 9.071428571 Simplifying a = 9.071428571
| 21(15+6a)=486 | | 21x(15+6a)=486 | | 5(4x-3)+8=-2 | | 2(x+3)=5(2-x)-2 | | (x-2)+4=6x-17 | | B=P(500-20P)-C(500-20P) | | q=500-20P | | 2x+x=51 | | 2x+6=10-5x-2 | | 34+x=-13 | | 5(x+5)= | | 2b=25-3b | | -14d-16=2(d+8)-12d | | 24d+20=116 | | 5(b+2)=8b-11 | | 0.5x+3=-x | | 3(x+6)+103=8x-5(x-5) | | -13d-21=3(d+7)-10 | | 13x+5(x+1)=18(x+1)-13 | | 3-9x=5x-4 | | 4x+x+1=6 | | 3x^2-(2k-3)x-2k=0 | | 5.68-4.61x-1.9x=23.908 | | 7+9+b=40 | | -7x=-26+6x | | 2b-60=20 | | 2y^2-11y+14= | | x(-9+x)=0 | | 3x-1=-16 | | 6k=84 | | 11x-3=4-4x | | 5(x+6)=20 |